Diplomasi Publik China Sebagai Upaya Mendukung One China Principle - Rizal Budi Santoso; Windy Dermawan (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2021)
Abstract This article aims to explain the Chinese public diplomacy towards the Taiwanese public as an effort to support one China principle. Researchers see that this one China principle is a stepping stone for China and Taiwan in establishing interactions based on the 1992 consensus. In analyzing, the researcher used the concept of Mark Leonard with the aim to find out how Chinese public diplomacy towards the Taiwanese public was in an effort to support one China principle. The research method used in this research is a qualitative method that is supported by collecting data through literature studies and also reducing the data in conducting data analysis. The results of this study indicate that Chinese public diplomacy towards Taiwan as an effort to support one China principle has gained support for this one China principle coming from the Kuomintang Party and Taiwanese businessmen based on the 1992 consensus.